2016
DOI: 10.1160/th16-03-0185
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolism in patients with hepatitis C

Abstract: Some studies suggest that patients with hepatitis C virus (HCV) infection have an increased risk of deep venous thrombosis (DVT) and pulmonary embolism (PE). Unfortunately, available data on this association are contrasting. A systematic review and meta-analysis of literature studies was performed to evaluate the risk of venous thromboembolism (VTE) associated with HCV. Studies reporting on VTE risk associated with HCV were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…aPL may easily alter this unstable balance, thus leading to thrombotic complications, as documented in hepatitis B and C patients with aPL positivity (50). In a recent meta-analysis, we have also documented an increased thrombotic risk in HCV patients, regardless the severity of liver dysfunction (52). Thus, a direct viral action could also be hypothesized, but this could only partially explain the increased thromboembolic risk associated with cirrhosis because limited to cases with viral aetiology.…”
Section: Discussionmentioning
confidence: 79%
“…aPL may easily alter this unstable balance, thus leading to thrombotic complications, as documented in hepatitis B and C patients with aPL positivity (50). In a recent meta-analysis, we have also documented an increased thrombotic risk in HCV patients, regardless the severity of liver dysfunction (52). Thus, a direct viral action could also be hypothesized, but this could only partially explain the increased thromboembolic risk associated with cirrhosis because limited to cases with viral aetiology.…”
Section: Discussionmentioning
confidence: 79%
“…Clinical studies have found that patients with cirrhosis are not protected against thrombotic events . Moreover, de novo portal vein thrombosis has been associated with high TG in the presence of TM .…”
Section: Discussionmentioning
confidence: 99%
“…The finding is comparable with other systematic reviews, which revealed a high prevalence of thrombotic events in viral diseases. 42 45 This high prevalence of thrombotic events could probably be due to the inflammatory process, cytokine storm, lung injury, and endothelial injury that increase the risk of hypercoagulable state in hospitalized COVID-19 patients. 46 Subgroup analysis based on patient characteristics revealed that the highest incidence of thrombotic events was observed in patients admitted to the intensive care unit (50%) (95% CI: 32–68) relative to patients admitted in medical wards.…”
Section: Discussionmentioning
confidence: 99%